COMPILATION OF GEOMORPHOLOGICAL MAP FOR RECONSTRUCTING THE DEGLACIATION OF ICE-FREE AREAS IN THE MARTEL INLET, KING GEORGE ISLAND, ANTARCTICA - Rosa, Kátia Kellem; Vieira, Rosemary; Mendes Júnior, Claudio Wilson; Souza Júnior, Enoil de; Simões, Jefferson Cardia (Revista Brasileira de Geomorfologia, 2013)
We compiled a geomorphological map and a reconstruction map of glacier extension and ice-free areas in the Martel Inlet, located in King George Island, South Shetlands, Antarctica. Glacier extension data were derived of the digitized over a orthophotomosaic (2003), SPOT (February, 1988; March, 1995 and 2000), Quickbird (October, 2006) and Cosmo-Skymed (February, 2011) images. This mapping was supported by fieldworks carried out in the summers of 2007, 2010 and 2011, and by topographic surveys and geomorphic map in the proglacial area. Several types of glacial deposits were identified in the study area, such as frontal and lateral moraines, flutes, meltwater channels and erosional features like rock moutonnés, striations and U-shaped valleys. These features allowed reconstructing the evolution of the deglaciation environment in the Martel Inlet ice-free areas, which has been affected by a regional climate warming trend. The mapped data indicated the glaciers in study area lost about 0.71 km² of their ice masses (13.2% of the 50.3 km² total area), without any advances during 1979-2011. Since those years these glaciers receded by an average of 25.9 m a-1. These ice-free areas were susceptible to rapid post-depositional changes.